ENGLISH REDUPLICATION IN THE MALAYSIAN CONTEXT - Mariam Mohamed Nor; Mohammad Hadi Bin Hamzah; Rahmad Sukor Ab. Somad (Al Qalam, 2009)
Reduplication is playful in certain languages while informative in others. The recent emergence of the form together-gather, single-mingle, calling-calling and laterlater brings forth the need to examine where and how the form emerged. The social contact Malaysians achieve is a vocabulary enriching mechanism just as how English has some 900,000 words. Also the catchy-ness of reduplicated words, for businesses' branding holds a key to an economically successful country. Also, this paper studies the feasibility of reduplicating rules, in particular of the English language and Bahasa.